A four-fold interpenetrated metal–organic framework as a fluorescent sensor for volatile organic compounds. Issue 38 (18th August 2016) - Zhao, Xiaoyu; Li, Yang; Chang, Ze; Chen, Long; Bu, Xian-He
Abstract : A highly luminescent four-fold interpenetrated 3D metal–organic framework based on an AIE active tetrakis(4-(pyridin-4-yl)phenyl)ethene ligand was facilely synthesized and thoroughly investigated. Abstract : A four-fold interpenetrated three dimensional (3D) metal–organic framework, [Cd2 (tppe)(bpdc)2 (H2 O)]·solvent (1 ), was synthesized with a tetraphenylethene (TPE)-based ligand, 1, 1, 2, 2-tetrakis(4-(pyridin-4-yl)phenyl)ethene (TPPE). This complex exhibits intense blue luminescence and is sensitive to toxic volatile organic compounds (VOCs).